Mejoramiento de los procesos de atención al cliente en el Hospital Dr: Aníbal González Álava Calceta - Bravo Calderón, Angélica Carolina (2013)
The research aimed to central process for improving customer services in admissions, emergency and laboratory at the Dr. Aníbal González Álava hospital in the city of Calceta, starting by applying tools, methods and techniques that show initial situation in patient satisfaction for their care received. Using tools for research, identified each of the shortcomings in delivering a quality service by evaluating the users, through a survey established indicators that focus more on patient dissatisfaction being the key point that was taken for the development of the proposed restructuring of customer in order to provide corrective actions for better performance and monitoring activities as giving sequence and implement processes to provide the service, encouraging the employee to improve the work environment in order to comply with the main objective is to improve the service to users and feel satisfied with the service received.